Предмет: Алгебра,
автор: anna890890
(х-2)^2(х^2-4х+3)=12
Решите уравнение, пожалуйста
Ответы
Автор ответа:
1
(x-2)²(x²-4x+3)=(x-2)²((x²-4x+4)-1)=(x-2)²((x-2)²-1)
Пусть (x-2)²=t, где t≥0. Тогда уравнение перепишется в виде t(t-1)=12 ⇒ t²-t-12=0 ⇒ t₁=-3<0 ∪ t₂=4.
Вернемся обратно к замене. (x-2)²=4 ⇒ |x-2|=2 ⇒ x-2=2 ∪ x-2=-2 ⇒ x=4 ∪ x=0
Ответ: 0; 4
Похожие вопросы
Предмет: Химия,
автор: tjover004
Предмет: Математика,
автор: viktorianasedkina
Предмет: Алгебра,
автор: viktoriyamakarchuk01
Предмет: Математика,
автор: uheelp